Lodo de esgoto: algumas aplicações em engenharia - Feitosa, Maria Celia Alves (2009)
The use of building residues has been consolidated as a way to get sustainability in civil construction industry as well as it has provided decreases in environmental impacts that arise from inadequate disposal of such material. Due to its specific production features, building industry has a large field where one can use these residues as raw material. The objective of this work is to contribute with studies about the possibilities of using sewage sludge as a way to improve colapsive soil features and as small size concrete aggregates. Sewage sludge with 25, 50 and 75 Mg ha-1 from Mangueira and Curado Treatment Plants were used with addition of about 5%, 10% and 15%. To obtain the characterization of sewage sludge properties and to analyze its interaction with the soil and the cement of concrete specimens several tests were performed, such as: physical and chemical tests, scanning electron microscopy tests, hydraulic conductivity tests, chemical mobility tests, compression strength tests, sclerometric tests and ultrasonic pulse velocity tests. Obtained results allowed concluding that the addition of sewage sludge in the soil contributed to decrease in its void index, improved its atomic packing factor, reduced its collapsibility to the same apparent specific dry weight showing, this way, that this procedure can be useful to improve collapsible soils performance. It was also observed that when one increases the proportion of sewage sludge in substitution to small size concrete aggregates the compression strength and water absorption decreases when compared to a concrete made with usual aggregates. In spite of being preliminary results, obtained behavior indicates that the use of sewage sludge in substitution to a part of small size concrete aggregate should be used with care, even in small buildings and advanced studies are needed to exploit its use as a building material